Isotopic ratios and concentrations of organic carbon in sediments, wood and plant fragments of ODP Leg 184 sites - Joel S Leventhal (PANGAEA, 2004)
Carbon isotopes were determined on the organic matter (OM) in sediments recovered from four sites (1143, 1144, 1146, and 1148) in the South China Sea during Ocean Drilling Program Leg 184. Concentrations of finely disseminated OM in the sediments were low (generally 0.1 to 0.5 wt%) and show organic d13C isotope values (generally -22 per mil to -24 per mil) indicative of marine to mixed marine and land-derived OM. The shipboard sedimentologists noted and the author collected seven samples of discrete centimeter-size chunks of organic carbon-rich material, such as fragments of wood, from cores from the five sites. The d13C values in these samples ranged from -24 per mil to -30 per mil. Humic material extracted from two wood/lignite samples and one plant fragment sample has nearly the same 13C value as the bulk material. The 13C values of humic extracts from the woody materials are different from those of marine materials, indicating that the extractable material is original, land-derived OM rather than absorbed/adsorbed OM from the marine environment. The d13C values (-28 per mil to -30 per mil) for the two plant fragment samples appear unusually light but are probably reasonable for nonwoody land-derived OM, which is rarely observed, preserved, or analyzed in deep-sea cores. Assuming carbon isotope values of -20 per mil for "pure" marine and -27 per mil for "pure" terrigenous OM, samples from Leg 184 generally preserve 40%-60% marine and 40%-60% terrigenous OM. However, because marine OM is more metabolizable than terrigenous OM and because these samples contain pyrite sulfur, the actual concentration of marine OM originally deposited with the sediments was probably in the range of 60%-90%.
Supplement to: Leventhal, JS (2004): Isotopic chemistry of organic carbon in sediments from Leg 184. In: Prell, WL; Wang, P; Blum, P; Rea, DK; Clemens, SC (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 184, 1-13, https://doi.org/10.2973/odp.proc.sr.184.215.2004